Sostenibilidad en la dinámica de Responsabilidad Social Empresarial en una perspectiva de estándares Gri en el contexto universitario en Colombia - García Mogollón , Javier Mauricio; Gamboa Suárez, Ramiro; Jiménez Rodríguez, Luis Alfredo (Mundo FESC, 2023)
Objective: To evaluate the use of the Global Reporting Initiative (GRI) standard and its ability to address social responsibility problems in the university context, determining the adaptation of internal management processes to changes in modern organizations and verifying corporate social responsibility. Methodology: A case study was carried out in a higher education institution through documentary review and qualitative research with an exploratory-descriptive design, using bibliometric consultation as the main technique. Findings and discussion: Some Colombian universities, both public and private, have adopted GRI standards to report on their performance in social, environmental and economic responsibility. However, only two universities in Colombia have fully implemented these standards. It was noted that instead of full GRI reports, some universities generate reports related to the Sustainable Development Goals (SDGs), which may confuse readers about true accountability. Conclusions: There is a commitment to transparency and accountability, but the methods and standards adopted vary. Although compliant sustainability reports have been developed, not all follow specific GRI guidelines. The lack of widespread adoption of GRI standards in most Colombian universities limits their potential as agents of social and environmental change, and contributes to less clear and effective accountability processes.